Real Madrid dan mentalitas juara: Rahasia dibalik 15 gelar Liga Champions UEFA - Saida, Mukhammad Fahmi Ulum (Maliki Interdisciplinary Journal, 2024)
Real Madrid is one of the most successful and famous football clubs in the world, with a winning mentality that is deeply rooted in the club’s culture and history. Real Madrid’s winning mentality is characterized by several key elements: an unyielding fighting spirit, strong belief in facing difficult situations, the ability to perform at crucial moments, and the desire to continue to excel in domestic and international competitions. This mentality is shaped by the club’s long history of success, starting from the Alfredo Di Stefano era to the modern era with star players such as Cristiano Ronaldo and Sergio Ramos. Strong leadership from coaches and team captains, as well as unwavering support from loyal fans, also play an important role in building and maintaining this mentality. Real Madrid’s winning mentality is not only visible in wins on the pitch, but also in how the club faces defeats and challenges, always seeking to bounce back and come back stronger. This mentality has led Real Madrid to many prestigious titles, including a record win in the UEFA Champions League, and made the club a symbol of success and excellence in the world of football.